WASOG 2023 conference highlights - Chuquimia, Olga D.; Rivera, Natalia V. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
The World Association of Sarcoidosis and Other Granulomatous Diseases (WASOG) 2023 conference held in Stockholm, Sweden, focused on disseminating the science and updating the interstitial lung diseases (ILDs) community with the latest science and concepts in precision medicine. This article summarizes the first four sessions of the conference that focused on disease and phenotype characterization, genetics in population cohorts, uses of biobanks and big data,  epidemiology in diverse racial and ethnic groups, and data-driven applications that can be applicable to move the ILD field toward precision medicine.